GIS-material for the archaeological project: Drottningmarken - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Vadstena municipality is planning an expansion of Vadstena city, covering a ca. 70 000 m2 big area in Drottningmarken. The Swedish National Heritage Board's Contract Archaeology Service, UV Öst, has performed an archaeological assessment (phase 2) to determine whether the area contains any archaeological remains. On the occasion of the survey, the assessment area had been staked out but only covering half of the original area. The farmer had not given permission to excavate the other half, and this part of the area was thus not investigated. If this area is to be developed in the future, further surveying must be performed. Trial trenches were dug in the surveyed part of the field. A few dark coloured patches were discovered, but were interpreted as being of natural origin.

Purpose:

The information in the purpose is translated from the archaeological report:
Due to a new local plan for Drottningmarken and by request of the County Administrative Board in Östergötland County, the Swedish National Heritage Board's Contract Archaeology Service, UV Öst, has performed an archaeological assessment (phase 2), to determine whether the development area contains any archaeological remains.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Vadstena kommun har för avsikt att planera ett ca 70 000 m2 stort område inom Drottningmarken för utbyggnad av staden. På grund av detta gav Länsstyrelsen i Östergötland i uppdrag åt Riksantikvarieämbetet UV Öst att utföra en arkeologisk utredning, etapp 2, för att avgöra om det nu aktuella exploateringsområdet innehåller lagskyddad fornlämning. Vid undersökningstillfället var området utstakat men endast hälften så stort i jämförelse med ursprungsplanen. Då andra hälften av området var nysått och lantbrukaren inte medgivit någon grävning på marken lämnades denna del utan undersökning. Om denna del kommer att exploateras i framtiden måste även det undersökas. Den nu undersökta åkerytan genomfördes som en sökschaktsgrävning. Någon enstaka mörkfärgning påträffades som tolkades vara av naturlig karaktär.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
På grund av kommande detaljplan inom Drottningmarken gav Länsstyrelsen i Östergötland i uppdrag åt Riksantikvarieämbetet UV Öst att utföra en arkeologisk utredning, etapp 2, för att avgöra om exploateringsområdet innehåller lagskyddad fornlämning.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Drottningmarken
Keywords: Modern age; nyare tid; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi